The Influence of One Stop Integrated Services and Quality of Public Services on Community Satisfaction in Minahasa Regency (Case Study at the Ministry of Religion Office of Minahasa Regency) - Pitoy, Handry; Pangkey, Itje; Langkay, Jeane (Technium Social Sciences Journal, 2024)
This research aims to determine the effect of one-stop integrated services and the quality of public services on community satisfaction in Minahasa Regency. This research uses a quantitative approach with three variables, namely one-stop integrated services (X1), public service quality (X2), and community satisfaction (Y). The population in this study was 226 people receiving services at the Ministry of Religion of Minahasa Regency with a sample of 144 people. This research method uses a quantitative research approach with an associative research type. The sampling technique in this research was a simple random sampling technique. The data collection technique is in the form of a questionnaire or questionnaire using a Likert scale and documentation. Test the research data analysis requirements using the normality test and linearity test. The data analysis technique uses multiple regression analysis because this research uses two or more independent variables, classical assumption test analysis, T test analysis to answer the first and second hypotheses, and F test to answer the third hypothesis. Data were analyzed using the SPSS v.22 program. Based on the results of data analysis in the T test, the one-stop integrated service variable partially influenced the community satisfaction variable by 3,966, and the public service quality variable partially did not influence the community satisfaction variable by 0.443. The F test shows the F count value is 8.063. The significant value of the integrated service (X1) and the quality of public services (X2) on community satisfaction (Y) obtained is 0.000. This significant value is smaller than the alpha value, namely 0.05, so H0 is rejected and H1 is accepted, meaning that one-stop integrated services and the quality of public services together influence public satisfaction. The coefficient determination (R2) of one-stop integrated services and the quality of public services on community satisfaction is 10.30%.